Outcome analysis of benign vocal cord lesions by videostroboscopy, acoustic analysis and voice handicap index - Thomas, George (Springer-Verlag, 2007)
Benign vocal cord lesions affect vibratory vocal fold function resulting in significant dysphonia. A prospective study of 30 patients with benign vocal fold lesions was undertaken at our centre to compare the pre and post operative voice using videostroboscopy, voice analysis and voice handicap index. The vibratory pattern of the cord improved as evidenced by the stroboscopic parameters-symmetry, mucosal wave and glottic closure (p<0.05). Voice analysis showed a trend towards normalcy but the values obtained did not attain statistical significance. Voice handicap index showed a reduction in the total and the subscales scores. Videostroboscopy along with acoustic analysis and voice handicap index are useful tools in the objective and subjective assessment of the effectiveness of treatment in patients with benign vocal cord lesions. Their routine use in a voice clinic is recommended.